A combined vaccine approach against Vibrio cholerae and ETEC based on outer membrane vesicles - Leitner, Deborah R.; Lichtenegger, Sabine; Temel, Philipp; Zingl, Franz G.; Ratzberger, Desiree; Roier, Sandro; Schild-Prüfert, Kristina; Feichter, Sandra; Reidl, Joachim; Schild, Stefan (Frontiers in Microbiology, 2015)
Enteric infections induced by pathogens like Vibrio cholerae and enterotoxigenic Escherichia coli (ETEC) remain a massive burden in developing countries with increasing morbidity and mortality rates. Previously, we showed that the immunization with genetically detoxified outer membrane vesicles (OMVs) derived from V. cholerae elicits a protective immune response based on the generation of O antigen antibodies, which effectively block the motility by binding to the sheathed flagellum. In this study, we investigated the potential of lipopolysaccharide (LPS)-modified and toxin negative OMVs isolated from V. cholerae and ETEC as a combined OMV vaccine candidate. Our results indicate that the immunization with V. cholerae or ETEC OMVs induced a species-specific immune response, whereas the combination of both OMV species resulted in a high-titer, protective immune response against both pathogens. Interestingly, the immunization with V. cholerae OMVs alone resulted in a so far uncharacterized and cholera toxin B-subunit (CTB) independent protection mechanism against an ETEC colonization. Furthermore, we investigated the potential use of V. cholerae OMVs as delivery vehicles for the heterologously expression of the ETEC surface antigens, CFA/I and FliC. Although we induced a detectable immune response against both heterologously expressed antigens, none of these approaches resulted in an improved protection compared to a simple combination of V. cholerae and ETEC OMVs. Finally, we expanded the current protection model from V. cholerae to ETEC by demonstrating that the inhibition of motility via anti-FliC antibodies represents a relevant protection mechanism of an OMV-based ETEC vaccine candidate in vivo.